2019
DOI: 10.1590/1806-9282.65.8.1055
|View full text |Cite|
|
Sign up to set email alerts
|

Causes of misdiagnosis in assessing tubal patency by transvaginal real-time three-dimensional hysterosalpingo-contrast sonography

Abstract: SUMMARY OBJECTIVE This study aims to investigate the causes of misdiagnosis in assessing tubal patency by transvaginal real-time three-dimensional hysterosalpingo-contrast sonography (TVS RT-3D-HyCoSy), in order to improve the diagnostic efficiency of TVS RT-3D-HyCoSy. METHODS A total of 162 oviducts of 83 infertility patients were examined by TVS RT-3D-HyCoSy. These results were compared with the gold standard for laparoscopic dye studies, and the misdiagnosed cases were analyzed. RESULTS TVS RT-3D-HyCo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 17 publications
(7 reference statements)
0
20
0
Order By: Relevance
“…The investigator needed to have enough experience on TVS 4D HyCoSy to make a comprehensive analysis of the observed conditions and finally give a diagnosis. The operator factor was one of the main causes of misdiagnosis, 26 HyCoSy's obvious interobserver variability is nonnegligible, 14 and HyCoSy results are highly dependent on the operator’ skill, 36 particularly in the judgement of the “partially passible” condition. Almost all of the diagnostic features of “partially passible” were subjective descriptions and judgments, such as slim, tortuous, slight spillage at the fimbria end of the tube, and others, indicating a lack of quantitative or semi‐quantitative objective evaluation indicators 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigator needed to have enough experience on TVS 4D HyCoSy to make a comprehensive analysis of the observed conditions and finally give a diagnosis. The operator factor was one of the main causes of misdiagnosis, 26 HyCoSy's obvious interobserver variability is nonnegligible, 14 and HyCoSy results are highly dependent on the operator’ skill, 36 particularly in the judgement of the “partially passible” condition. Almost all of the diagnostic features of “partially passible” were subjective descriptions and judgments, such as slim, tortuous, slight spillage at the fimbria end of the tube, and others, indicating a lack of quantitative or semi‐quantitative objective evaluation indicators 37 …”
Section: Discussionmentioning
confidence: 99%
“…4D HyCoSy is accurate as it visualizes the entire volume of the tube to portray the contrast throughout the tube. The accuracy of 4D HyCoSy increases to 87.5%–97.7% 7,23,25–26 …”
Section: Introductionmentioning
confidence: 96%
“…However, some false-positive or inconclusive diagnoses can occur due to poor image quality or an inappropriate initial transverse plane on TVS-4D-HyCoSy [8,12], which can lead to a series of unnecessary interventions, such as laparoscopy. The appropriate initial plane is critical to the success of volume imaging.…”
Section: Introductionmentioning
confidence: 99%
“…However, it requires the region of interest to encompass the full course of the fallopian tube, not merely the fimbrial end. It has been reported that the position and morphology of the fallopian tube can influence the image quality and that different diagnostic methods should be applied to improve the diagnostic accuracy [8,12]. A few specific cases of the Fallopian tubal position have been reported [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…The medical definition of female infertility is that no contraceptive measures have been taken for more than one year, and the sexual life is normal without a successful pregnancy. Besides, it is mainly divided into primary infertility and secondary infertility [ 1 ]. There are many causes of female infertility, mainly including ovulation disorders, fallopian tube factors, and abnormal endometrial receptivity.…”
Section: Introductionmentioning
confidence: 99%